Factors Influencing Cervical Cancer Screening Uptake among Reproductive-Aged Filipino Women: Findings from the 2022 Philippines National Demographic and Health Survey - Wah Wah Myint; Roaa Aggad; Qiping Fan; Sara E. Mendez (Women's Health Reports)
Background: Cervical cancer (CC) is the fourth leading cause of death among cancer cases and women intimate partner violence (IPV) survivors are more likely to experience CC-related mortality. This study aims to evaluate the factors influencing CC screening uptake among reproductive-aged women, especially among IPV survivors in the Philippines. Method: We used the 2022 Philippines’ National Demographic and Health Survey. The outcome variable was undergoing CC screening. The independent variables were different types of IPV, sociodemographic characteristics (age groups, place of residency, education level, wealth quintile, marital status, religion, employment), and other important variables (number of sexual partners, number of children, and access to health care). Descriptive statistics and multivariable logistic regression analyses were performed to examine influencing factors of CC screening. Results: The results revealed that approximately 10% (n = 1,648) of the women who participated in the survey had screened for CC. The results showed that women who experienced at least one type of IPV (adjusted odds ratio [aOR] = 1.32, 95% confidence interval [CI] = 1.08–1.62), aged 45–49 years (aOR = 6.42, 95% CI = 2.60–15.54), higher education (aOR = 14.26, 95% CI = 3.28–61.99), wealthier (aOR = 3.46, 95% CI = 2.54–4.72), having current employment (aOR = 1.30, 95% CI = 1.08–1.57), and having more than five lifetime sexual partners (aOR = 3.16, 95% CI =1.00–9.97), were more likely to undergo CC screening than their counterparts. Conclusion: Future CC screening initiatives should prioritize women with lower educational and socioeconomic backgrounds to effectively bridge the gaps in health disparities.